Using Bat Cave Vulnerability Index (BCVI) to determine cave conservation priorities in the Tuban Karst Area, East Java, Indonesia - TATAG BAGUS P. PRAKARSA; SUHARTINI SUHARTINI; RIZKA APRIANI PUTRI; FAILASUF A. NUGROHO (Society for Indonesian Biodiversity, 2025)
Abstract. Prakarsa TBP, Suhartini, Putri RA, Nugroho FA. 2025. Using Bat Cave Vulnerability Index (BCVI) to determine cave conservation priorities in the Tuban Karst Area, East Java, Indonesia. Biodiversitas 26: 5040-5048. Bats are keystone species in cave ecosystems, acting as major providers of energy that sustain diverse cave-dependent communities. Their presence and diversity make caves crucial habitats for broader ecosystem stability. In the Tuban Karst Area, East Java, Indonesia, where caves host high species diversity and endemism, bats play a central role in maintaining ecological balance. However, this ecosystem faces severe threats from ongoing habitat destruction. Identifying caves that should be prioritized for conservation requires an understanding of bat diversity, endemism, behavior, and conservation status, as well as a standardized mechanism for risk evaluation. This study aimed to determine cave conservation priorities in the Tuban Karst Area through a holistic rapid assessment using the Bat Cave Vulnerability Index (BCVI) with an index ranging from high to low conservation priority: 1A, 1B, 1C, 1D, 2A, 2B, ..., 4D. Sampling was conducted purposively in five caves: Lawa Belik, Srunggo, Jingkat, Ngerong, and Akbar. Data were analyzed using the BCVI method, which integrates biotic potential and vulnerability, represented primarily by bat species diversity and cave exposure to threats. The caves were ranked from highest to lowest conservation priority as follows: Ngerong (1A), Lawa Belik (2B), Akbar (3A), Srunggo (3B), and Jingkat (3C). This study demonstrates the significance of caves as bat roosting habitats. These findings highlight the critical role of bats in guiding cave conservation strategies and provide an evidence-based framework for prioritizing management actions in caves with the highest BCVI scores.